2019
DOI: 10.3389/fendo.2019.00223
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic and Elastographic Features of Extra- and Intrathyroidal Ectopic Thymus Mimicking Malignancy: Differential Diagnosis in Children

Abstract: Thyroid nodules with ultrasound (US) cancer risk features and extra-thyroid lesions suggesting malignant lymph nodes, require prompt diagnosis, especially in children. The US pattern of intrathyroidal ectopic thymus (IET) can strongly suggest papillary thyroid carcinoma (PTC). The extra-thyroid ectopic thymic tissue (EET) can mimic pathological lymph nodes in US. The aim of the study has been to demonstrate US features and diagnostic methods, allowing finally to confirm the presence of IET and EET in children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 20 publications
6
30
0
Order By: Relevance
“…Some studies have confirmed that the presence of an intrathyroidal thymus through cytology or surgery due to the fear that children with suspicious thyroid lesions are misdiagnosed ( 4 5 12 13 15 16 21 22 ). However, a few studies on the ultrasound characteristics and the prevalence of intrathyroidal thymus were based on US images only, without cytological evaluation, and suggested that US could be used as a common diagnostic tool to identify a benign intrathyroidal thymus ( 11 13 17 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have confirmed that the presence of an intrathyroidal thymus through cytology or surgery due to the fear that children with suspicious thyroid lesions are misdiagnosed ( 4 5 12 13 15 16 21 22 ). However, a few studies on the ultrasound characteristics and the prevalence of intrathyroidal thymus were based on US images only, without cytological evaluation, and suggested that US could be used as a common diagnostic tool to identify a benign intrathyroidal thymus ( 11 13 17 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The thymus has certain characteristic ultrasonographic features, which include a homogeneous background echogenicity similar to that of the liver or spleen, with scattered hyperechoic foci resembling a starry sky ( 4 5 6 7 8 9 10 ). Ectopic thymic tissue can be located anywhere along the descending path of the thymopharyngeal ducts ( 5 11 12 ). When ectopic thymic tissue abuts on the inferior or posterior surface of the thyroid or is enclosed by the thyroid parenchyma, the thymus is described as intrathyroidal ( 4 5 6 7 8 9 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thymus is the primary lymphoid organ in infancy and early childhood and facilitates the differentiation and maturation of T lymphocytes [1]. The thymus arises from the third pharyngeal pouch, eventually forming thymic primordial that descends into the anterosuperior mediastinum.…”
Section: Introductionmentioning
confidence: 99%